The prescribing pattern of sodium-glucose cotransporter-2 inhibitors and glucagon-like peptide-1 receptor agonists in patient with type two diabetes mellitus: A two-center retrospective cross-sectional study - Korayem, Ghazwa B.; Alshaya, Omar A.; Alghamdi, Albandari A.; Alanazi, Shahad S.; Almutib, Renad T.; Alsaileek, Mahdi; Alrashidi, Abdulrahman; Aldosari, Nasser; Bin Sheraim, Nader; Al Yami, Majed S.; Almohammed, Omar A. (Frontiers in Public Health, 2022)
Background The use of sodium-glucose cotransporter-2 inhibitors (SGLT2i) and glucagon-like peptide-1 receptor agonists (GLP-1 RA) in patients with type 2 diabetes mellitus (T2DM) remains limited, especially in those with other compelling indications. Thus, this study aimed to describe the prescribing patterns of GLP-1-RA and SGLT2i in patients with T2DM and to determine the factors that affect the prescribing of these medications. Methods This multicenter retrospective cross-sectional study reviewed the electronic health records of adult patients diagnosed with T2DM who received care between January and December 2020. The patients were classified according to their compelling indications into “patients who are more likely” to benefit from SGLT2i or GLP-1 RA and “patients who are less likely” to benefit from them. They were then further categorized depending on whether these medications were prescribed. Results A total of 1,220 patients were included; most were female (56.9%). SGLT2i or GLP-1 RA were preferably prescribed in only 19% of the patients for reasons including BMI ≥ 27 kg/m2 (85.6%), uncontrolled T2DM (68.5%), high risk for ASCVD (23.9%), or established ASCVD (14%). The remaining 81.0% were underprescribed these agents. Patients at an older age or with a history of stroke or transient ischemic attack had higher odds of being underprescribed (OR 1.02; 95% CI: 1.01–1.03 and OR 2.86; 95% CI: 1.33–6.15), respectively. Conclusion The results concur with those of previous studies highlighting the underutilization of GLP-1 RA and SGLT2i in patients with T2DM but also with compelling indications. To optimize the use of GLP-1 RA and SGLT2i for their additional benefits, prescribers need to assess the benefits of using these agents in patients who would likely benefit from them, regardless of DM control.